Emotions during times of disruption - Troth, Ashlea C.; Ashkanasy, Neal M.; Humphrey, Ronald H. (Research on emotion in organizations ;, 2023)
The COVID pandemic has swept through the world with significant consequences for our work and family lives. We have seen a huge upsurge in remote working, collaborating and leading and ways of working, giving rise to myriad challenges such as "Zoom fatigue," poor "digital demarcation," shifting workplace power balances, and declining mental health and safety. Its impact has rightly increased scholarly and practitioner attention towards better ways to support and understand employees, leaders, and organizations; and to help them to develop more effective responses to disruption of various forms. For volume 18 of the series Research on Emotion in Organizations we have fittingly chosen the theme, Emotions during Times of Disruption and contend that emotions and other affect related concepts represent keys to understanding the phenomena of disruption in organizations more fully. Literature to date addressing this issue is surprisingly scant and so chapters in this volume provide impactful and important contributions to an underexplored area. Emotions during Times of Disruption progresses through 4 thematic sections which include, Emotions in disruptive contexts, Emotions and performance-related outcomes during disruption, the role of supervisors and leader emotions during disruption and lessons learnt which help point the way forward with further insights and recommendations.